Crime scene [compact disc, unabridged] : a novel - Kellerman, Jonathan; Kellerman, Jesse (Kellerman, Jonathan. Clay Edison series., 2017)
Eccentric, reclusive Walter Rennert lies cold at the bottom of his stairs. At first glance, the scene looks straightforward: a once-respected psychology professor, done in by booze and a bad heart. Clay Denison is illicitly drawn to the victim's daughter, Tatiana, as he digs deeper into the case.